Introducing N-Heteroaromatic Bases into Copper(II) Thiosemicarbazon Complexes: A Way to Change their Biological Activity [Articol] - Ulchina, Ianina; Graur, Vasilii; Țapcov, Victor; Ciumacov, Iurie; Garbuz, Olga; Burduniuc, Olga; Ceban, Emil; Gulea, Aurelian (My University, 2022)
Three new copper(II) complexes, [Cu(1,10-Phen)(L)] (1), [Cu(2,2’- Bpy)(L)] (2) and [Cu(3,4-Lut)(L)] (3), where H2L=2-[(2,4- dihydroxyphenyl)methylidene]-N-(prop-2-en-1-yl)hydrazine-1- carbothioamide, 1,10-Phen=1,10-phenanthroline, 2,2’-Bpy= 2,2’-bipyridine, 3,4-Lut=3,4-lutidine, have been synthesized and characterized by elemental analysis, FTIR spectroscopy and single crystal X-ray crystallography (1, 2). All compounds are mononuclear. The introduction of a monodentate N-heteroaromatic base (3,4-dimethylpyridine) has led to a significant increase of antimicrobial activity against Gram-negative Escherichia coli and antifungal activity against Candida albicans compared to the pro-ligand and the precursor complex [Cu- (L)H2O]. The introduction of bidentate N-heteroaromatic bases did not lead to such increase of antimicrobial and antifungal activities. Moreover, complex 3 surpasses the inhibitory activity of tetracycline toward Enterobacter cloacae and the inhibitory activity of fluconazole toward Candida parapsilosis and Cryptococcus neoformans. The study of antioxidant activity against cation radicals ABTS* + showed that complexes 1–3 are more active than Trolox, but only introduction of the monodentate Nheteroaromatic base (3,4-dimethylpyridine) led to the increase of antioxidant properties compared to the precursor complex.
Keywords: antimicrobial and antifungal activities; antioxidants; copper complex; N-heteroaromatic bases; thiosemicarbazone